Tax lien sales as local neoliberal governance strategy: The case of Waterbury, Connecticut - Botein, Hilary; Heidkamp, C Patrick (Local Economy, 2013)
This article examines bulk sales of municipal property tax liens in the formerly industrial city of Waterbury, Connecticut, USA, in the 1990s, in order to explore the limits and contradictions of neoliberal local governance strategies. In the USA, cities and states create property tax liens by reducing delinquent real estate taxes to a judgment that creates a legal claim against the property at issue. We argue that Waterbury's efforts to resolve its fiscal stress by enhancing short-term revenues ultimately further constrained its revenue base, the tax lien sales reflected a spatial selectivity that created barriers to revitalization when neither the city nor tax lien purchasers had incentives to foreclose on distressed properties in struggling neighborhoods, and the tax lien sales' failure to resolve the city's budget crisis set in motion new efforts at tax base enhancement through real estate-led development in the central business district that also were unsuccessful. © The Author(s) 2013 Reprints and permissions: sagepub.co.uk/journalsPermissions.nav.
Keywords: dept.egm; housing; local government; neighbourhood decline; neoliberalism; real estate taxes; tax liens; urban governance